Analisis Perbandingan Desain Geometri Pin Bahan Bakar Heksagonal dan Persegi GFR Menggunakan Bahan Bakar Uranium Karbida - Maulana, Muhammad Rizqi; Syarifah, Ratna Dewi; Prasetya, Fajri; Mabruri, Ahmad Muzaki; Arkundato, Artoto; Rohman, Lutfi (Departement of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2024)
Comparative Analysis of Hexagonal and Square GFR Fuel Pin Geometry Designs with Uranium Carbide Fuel has been carried out. Nuclear reactors from Generation I to IV have developed significantly, with Gas-cooled Fast Reactors (GFR) being a potential candidate for operation by 2030. This study focuses on a GFR reactor utilizing uranium carbide (UC) fuel with a low input power of 300 MWth. The reactor core adopts a cylindrical pancake geometry with 100 cm height and 240 cm diameter dimensions. The objective is to compare the optimal design between hexagonal and square pin cell geometries for GFR-type fast reactors. The study employs the SRAC 2006 software with the JENDL 4.0 database. The research involves homogenous core configuration calculations, heterogeneous core configuration calculations, and variations in fuel fraction to determine optimal data for hexagonal and square pin cell configurations. Results indicate that heterogeneous fuel configurations require fuel fractions of 51% for hexagonal pins and 59% for square pins, with comparable maximum power performance at End of Life (EOL) and Beginning of Life (BOL). It suggests that hexagonal pins are more efficient, requiring less fuel material to maintain reactor criticality over a 20-period burn-up.